Assessment of Respiratory Quality among Batik Artisans: as a Safety Education for The Workers - Evi Widowati; Khansa Putri Aprilia; Salsa Dilla Amanda Putri; Muthia Muthia; Azradina Fakhira; Yuliati Yuliati; Michelle Seaw Seak Fong (Journal of Safety Education, 2023)
As the production and usage of chemicals in workplaces around the world increases, workers are more at risk of toxicant chemical exposures that may be harmful to their health, this includes in the use of paraffin wax in Batik industry. The aim of this research is to analyze the relationship between respiratory quality and toxicant in the process of batik production. The sample of this research consisted of 5 batik workers. The data were collected using an interviewer administered structured questionnaire and the measuring of Peak Expiratory Flow Rate (PEFR) using peak flow meter about toxicant exposure and the application of occupational safety and health related to toxicant. The variable of this study was the respiratory quality of the workers towards toxicant exposure. The results showed that there were both positive and negative correlations between exposure to toxic substances and the workers, depending on their age, sex, and duration of exposure. However, we recommend implementing control measures to improve the quality of work for the workers.